An Analysis of Subtitling Strategy Used in The Revenant Movie (2015) - Akbar, Muhammad Kharisma; , Dr. Dwi Harjanti M. Hum (2016)
This research focuses on the subtitling strategy analysis in The Revenant using Gottlieb's theory about subtitling strategy and Nababan's theory about subtitling Quality. The objectives of this research are (1) to identify the subtitling strategies found in The Revenant(2015) movie and (2) to describe the subtitling qualityofThe Revenant (2015) movie. The type of this research is descriptive qualitative. The object of this research is the The Revenant(2015)movie script. The researcher uses documentation and interviewing technique to collect the data. The researcher uses triangulation to prove the validity of the research where the data sources are from movie and informant. The researcher obtains 834 data which use subtitling strategies in The Revenant(2015)movie script. There are Paraphrase 11.27%, Transfer 64.39%, Imitation 14.27%, Condensation 6.83%, Deletion 0.36%, and Resignation 0.12% and Transcription 0.12%. The most subtitling strategy used is Transfer, because the subtitler translates the source text completely and accurately. Three aspects for good quality that subtitling should fulfill: accuracy, acceptability, and readability. From 834 total counts of data there are 672 data or 80,5% to accurate, 156 data or 18,7 % to less accurate, 6 data or 0,7 % to inaccurate, 754 data or 90,4 % to acceptability, 74 data or 8,9 % to less acceptability, 6 data or 0,7% to unacceptability, 777 data or 93,1 % to high readability level, 54 data or 6,5 % to moderate readability level, 3 data or 0,3 % to low readability level.